2009
DOI: 10.1086/605037
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Gastroenteritis in Children in 4 Regions in Brazil: A Hospital‐Based Surveillance Study

Abstract: The prevalence, seasonality, and genotype distribution of rotavirus infection varied in different regions in Brazil. With immunization programs, continuous monitoring of rotavirus types is important to detect novel and emerging strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 26 publications
5
33
1
7
Order By: Relevance
“…Knowing that rotavirus serotypes can vary from region to region, these effectiveness projections used the most recent rotavirus surveillance data from four regions of Brazil to obtain each region's weighted serotype-specific effectiveness (Munford et al 2009). The sensitivity analysis also accounted for variations in the effectiveness against mixed and non-typeable serotypes that may also affect overall vaccine effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing that rotavirus serotypes can vary from region to region, these effectiveness projections used the most recent rotavirus surveillance data from four regions of Brazil to obtain each region's weighted serotype-specific effectiveness (Munford et al 2009). The sensitivity analysis also accounted for variations in the effectiveness against mixed and non-typeable serotypes that may also affect overall vaccine effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Serotype data used in this model included published hospital rotavirus surveillance data collected in four cities from different regions in Brazil -Goiânia, Porto Alegre, Salvador and São Paulo -from [2005][2006], providing the proportions of rotavirus attributable to serotypes G1, G2, G3, G4 and G9 (Table I) (Munford et al 2009). The model inputs for baseline serotype-specific vaccine efficacy were derived from the large-scale RV5 clinical trial, REST, that demonstrated the efficacy against RGE-related hospitalisations and emergency department (ED) visits for serotypes G1 [95%; 95% confidence interval (CI) 91.6-97.1], G2 (88%; 95% CI < 0-98.5), G3 (93%; 95% CI 49.4-99.1), G4 (89%; 95% CI 52.0-97.5) and G9 (100%; 95% CI 67.4-100.0) check the efficacy among infants from 11 countries (United States, Finland, Germany, Belgium, Sweden, Italy, Jamaica, Costa Rica, Mexico, Puerto Rico and Guatemala) (Vesikari et al 2006, Munford et al 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive samples were molecularly analyzed. Results: RVA positivity was 16.9%, with a predominance of G2P [4]. Periods: pre-vaccination: predominance of IId (G1), IId (G2) lineages, and I1 and E1 genotypes; post-vaccination: predominance of Ib (G1), IIa, and IIc (G2) lineages and I2 and E2 genotypes.…”
mentioning
confidence: 99%
“…No statistical signifi cances were observed between the positivity rates and gender (p = 0.7418), age (p = 0.5895), symptoms (p = 0.2416), or vaccination status (p = 0.6793), although a higher detection rate was detected among unvaccinated children (23.1%) compared to vaccinated children (15.4%). Of the 11 positive samples, 4 were characterized as G2P [4], 6 were G2PNT (not genotyped), and 1 was GNTP [9][11]. Table 1 shows that of the 6 archived samples obtained before the introduction of the vaccine in Brazil, 5 were characterized as G1P [8] and 1 was G2PNT.…”
mentioning
confidence: 99%